Pengelolaan Penataan Arsip Bagian SDM dan Umum PT. PELINDO IV (PERSERO) Cabang Balikpapan - Sari Rahmawati; Alisa Alsina; Darna Astriana (Jurnal Mahasiswa Kreatif, 2023)
Archiving is a process or activity that starts from creation, receipt, collection, regulation, control, maintenance, care, and storage as well as evaluation according to a certain predetermined system. As time goes by and also the many activities that have been carried out at PT Pelindo IV (Persero) Balikpapan Branch, more and more archives have been created. The purpose of this study was to find out the causes of archive management and to find out the efforts made in overcoming obstacles to archive management in the HR and general division at PT Pelindo IV (Persero) Balikpapan Branch. The type of research used in this research is descriptive research with a qualitative approach in which data is collected through observations, interviews, and documentation. Based on the research results, several things can be improved for more efficiency and effectiveness in archiving 1) What can be improved is the system currently used. Pelindo IV (Persero) Balikpapan Branch, namely the system regarding this is quite good, it's just that in recovering it is still difficult to find because letters are in other classification sections such as payment archives in the information system classification. 2) Tools and equipment used in managing archives are wooden and glass cabinets. The arrangement is still disorganized because the order folders are just piled up. The archive storage space is too small so many archives accumulate and cannot be put in the cupboard. 3) There are still many archives whose duration of archive destruction is too long, considering the number of incoming documents or document production is quite high and quite a lot because archives that are old and no longer needed will be destroyed within a yearly period.